A Multicenter Study on Etiology of Acute Pancreatitis in Beijing During 5 Years. Issue 3 (April 2015) - Zheng, Yamin; Zhou, Zhen; Li, Haichao; Li, Jia; Li, Ang; Ma, Binrong; Zhang, Taiping; Liao, Quan; Ye, Yingjiang; Zhang, Zhongtao; Yang, Yinmo; Wang, Zhenjun; et al.
<x xml:space="preserve">Abstract</x> Objectives The aim of this study was to determine the etiology tendency of acute pancreatitis (AP) in the Beijing region and the relationship with influencing factors. Methods This retrospective multicenter study enrolled 8 representative general hospitals from January 1, 2006 to December 31, 2010. The etiology tendency was analyzed, and the relationship was defined with sex, aging, severity, mortality, recrudesce rate, length of stay, and hospitalization cost. Results The study enrolled 2461 patients. The total number was increasing year by year. Causes included biliary (1372, 55.75%), alcoholism (246, 10%), hypertriglyceridemia (255, 10.36%), and the others (588, 23.89%). Biliary AP was the most frequent primary cause. Hypertriglyceridemic AP increased at a faster rate than alcoholic AP. There was higher proportion of alcoholic and hypertriglyceridemic AP in men than in women. There is an increase of AP patients with ages 40 to 49 years and older than 70 years. Alcoholic and hypertriglyceridemic AP were higher in patients younger than the age of 50 years, and biliary pancreatitis was higher in patients older than 70 years. Severe AP was classified among 736 patients (29.9%). Etiology distribution was different between severe AP and mild AP (P < 0.001). Mortality in the hospital was 1.54%, and there was no difference in each group. Recrudesce of hypertriglyceridemic AP was higher (P < 0.01). Conclusions Acute pancreatitis patients increased year by year in Beijing. Gallstones were the predominant etiological factor. There were different etiology proportion of AP according age, sex, and severity.